Penguatan Manajemen pada Usaha Kerajinan Bambu Jihan Craft Desa Somakaton - Najmudin Najmudin; Sri Lestari; Lasmedi Afuan; Devani Laksmi Indyastuti (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Partners in this program are bamboo craftsmen Jihan Craft, Somakaton Village, Somagede District, Banyumas Regency. The problems faced by partners are lack of equipment in running their business; very limited capabilities in business management consisting of production management, HR, marketing and finance; limited ability in bookkeeping and financial reporting; limited ability to carry out online marketing activities; do not form groups; do not understand group management; and do not have the skills to carry out group administration. To achieve the goals, activities are carried out in the form of counseling, practice and mentoring. The evaluation method is carried out by comparing the level of knowledge and abilities as well as the production and marketing performance of partners before and after the activity. The benefits of this service activity are that partners get additional mechanical production equipment so they can increase the quantity and quality of their products and can produce more efficiently, partners' business management abilities increase, they have the ability to do bookkeeping and financial reporting, they can carry out online marketing activities well, the formation of groups Jihan Craft business officially, understand and can practice group management well; and can carry out group administration activities well.